Exploring the Effect of Digital Game Based Learning on Young Learners’ Vocabulary - Suta, I Putu Manggala Bayu (Universitas Pendidikan Ganesha, 2025)
Vocabulary is one of the language aspects that can be practiced everywhere. However, Vocabulary learning is a complex and gradual process. Many EFL students find it difficult compare to other aspect. Integrating MALL in vocabulary instruction proves to be a promising approach to help the students with their comprehension. This present research aims to investigate the effective Digital Game Based Learning in teaching Vocabulary for young learner. This study used library research as the methodology in collecting the data. The results of the previous study will be stated first then it will be discussed to find the effective Digital Game Based Learning in teaching Vocabulary for young learner. The result shows that Kahoot and Quizizz is the best platform to be used in teaching vocabulary to young learner since both of the platforms offers suitable features for young learners.